OPTIMALISASI IZIN PBG RUMAH TINGGAL: STUDI KASUS STRATEGI DINAS PERUMAHAN RAKYAT DI KOTA SURABAYA - Muhammad Ridho Rifansyah (Halu Oleo University, 2025)
A Building Permit (PBG) is a permit that must be obtained by the building owner when constructing a building. In Surabaya City, especially in Kenjeran Sub-district, many residential buildings are found without PBG, indicating the need for a strategy to control PBG licensing. This research aims to see how DPRKPP's strategy in increasing the number of PBG permits for residential houses in Kenjeran Sub-district, Surabaya City. This research uses qualitative research methods with the data collection process in the form of interviews, observations, documentation and literature studies. Based on the findings of the study, which uses the concept of strategic management according to Fred R. David and Forest R. David, it is known that the formulation of DPRKPP's strategy has a clear foundation through vision, mission, regulation and long-term goal setting. However, the strategy implementation process has not been optimal because DPRKPP is still faced with various internal and external challenges. Furthermore, the lack of active evaluation down to the sub-district level has made the implemented strategy less adaptive and certainly less optimal.